2013
DOI: 10.3109/13668250.2013.861393
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention of allied health professionals in the disability sector in rural and remote New South Wales, Australia

Abstract: Background People with disability living in rural areas are vulnerable to the loss of access to allied health services due to a critical shortage of allied health professionals (AHPs). This study aimed to investigate recruitment and retention issues of importance to AHPs providing services to people with disability in rural New South Wales, Australia. Method Focus groups and semistructured interviews were conducted with 97 purposively sampled service providers in the disability sector. Interviews and focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…As reported by other rural studies of service provision for people with disabilities, it is difficult to build relationships with clients when there is a high staff turnover [40,47]. Lincoln et al [12] in their study of allied health workers in the state of NSW found that practitioners in rural and remote areas feel the pressure of an immense workload, they can experience frustration and embarrassment at the long waiting lists, and they lack the ability to prioritise patients themselves due to policy constraints. These feelings are compounded in small communities when professionals see their clients around the township [48].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As reported by other rural studies of service provision for people with disabilities, it is difficult to build relationships with clients when there is a high staff turnover [40,47]. Lincoln et al [12] in their study of allied health workers in the state of NSW found that practitioners in rural and remote areas feel the pressure of an immense workload, they can experience frustration and embarrassment at the long waiting lists, and they lack the ability to prioritise patients themselves due to policy constraints. These feelings are compounded in small communities when professionals see their clients around the township [48].…”
Section: Discussionmentioning
confidence: 94%
“…Beyond the time and energy expended in seeking relevant information, parents are also challenged both physically and emotionally when accessing disability services, with service delivery often being haphazard and beset with organizational issues [7][8][9][10][11][12]. Access to resources is very important for families to be able to cope, but the processes of obtaining these resources often seems so stressful that they are not always utilised [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…Data on retention of health professionals in Uganda is reported as inadequate; however some of the top strategies that are thought to support retention are: providing accommodation, providing salary top-up for health care providers willing to work in hard-to-reach areas, improving the style of supervision and management, education and training opportunities for health workers, improving work conditions, providing social needs support, and health and access to antiretroviral treatment (ART) [2, 3, 6, 15–18]. Despite all these strategies having been tried, significant shortage of health professionals still remains a big challenge [19, 20], especially having trained health professionals retained in remote rural areas [21, 22]. Within the decentralized healthcare system of Uganda, each of the districts has a well established system of health facilities from level five (district hospitals) at the district headquarters to level one at the village level.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, NSW had 24 percent fewer AHP positions per head of population in rural and remote areas than the state's average 10 . Rural AHPs in NSW may travel thousands of kilometres in a year 11 , a factor in low retention rates and recruitment difficulties 12,13 . In regional and remote regions of NSW, people with disabilities and their carers were found 11 to greatly value speech pathology and other allied health services while highlighting the levels of unmet need, long waiting lists, lack of continuity and consistency in services, and difficulties in accessing therapy.…”
Section: Rural and Remote Australiamentioning
confidence: 99%